2018
DOI: 10.1007/s10896-018-0019-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Support in the Link Between Economic Abuse and Economic Hardship

Abstract: More data is needed about the pathways through which intimate partner violence (IPV) impacts the economic well-being of survivors. The current study assesses the moderating influence of social support on the association between economic abuse (EA) and economic hardship. Female participants (n = 435) were recruited to participate in a web-based survey which included standardized measures of EA, other forms of IPV, domains of social support, and economic hardship. Analysis included bivariate and multivariate reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Moreover, given the results of the Wilcoxon–Mann–Whitney U test, we found that the IPV experiences group was significantly more likely to anticipate needing more help and cooperation from family, friends, and neighbors than the non-IPV experiences group. Prior studies in disasters and IPV have noted the protective role of social support for those experiencing both disaster and IPV ( Kaniasty, 2012 ; Voth Schrag et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given the results of the Wilcoxon–Mann–Whitney U test, we found that the IPV experiences group was significantly more likely to anticipate needing more help and cooperation from family, friends, and neighbors than the non-IPV experiences group. Prior studies in disasters and IPV have noted the protective role of social support for those experiencing both disaster and IPV ( Kaniasty, 2012 ; Voth Schrag et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The participants' responses have key implications for praxis among clinicians and helpline workers and highlight generative areas of future investigation in scholarly literature. Domestic violence literature underscores IPV's negative impact on the stability of survivors (Adams et al 2013;Goodman et al 2009;Voth Schrag et al 2020) and the importance of developing an individualized plan of action to address abuse based on the lived experiences of survivors (Voth Schrag 2019). The first identified need, to identify what causes abusive episodes, indicates participants' selfawareness regarding their difficulties with differentiating abuse from normal stress responses and tendency to make allowances according to cultural beliefs and entrenched gender roles.…”
Section: Discussionmentioning
confidence: 99%
“…Although useful, scholarly research on intention to stay or leave has not yet translated effectively to praxis. Past research underscores IPV's negative impact on the stability of survivors (Adams et al 2013;Goodman et al 2009;Voth Schrag et al 2020) and the importance of developing an individualized plan of action to address abuse (Voth Schrag 2019). Following Storer et al (2018) by focusing on participants' lived experiences with IPV, this study's methodology facilitated analysis of in-depth, narrative responses from a relevant sample.…”
Section: Leave-stay Researchmentioning
confidence: 99%
“…The variety of theories and conceptual models found reinforces the scope of the theme that has been studied from different perspectives and theoretical lenses. A brief selection of theories connected to the elements of female financial well‐being can give an overview of this picture—namely, human capital theory, cited especially in works that assessed the impact of motherhood on women’s work experience and skill development (Budig & England, 2001; Gangl & Ziefle, 2009); cumulative disadvantage theory, referenced in studies that addressed the development of inequalities, especially when women accumulate different vulnerabilities, such as being black, poor and a single mother (Lee et al., 2015; Wakabayashi & Donato, 2006); coercive control theory, which was present in one article on violence against women (Schrag et al., 2020); and the male breadwinner model and social role theory, cited in articles that explored social issues related to gender roles for men as male breadwinners (Eirich & Robinson, 2017) and for women, which are more likely to assume economic dependency roles (Fan & Babiarz, 2019). A complete list of the explicitly mentioned theories, models and frameworks is presented in Table 5.…”
Section: Publication Trendsmentioning
confidence: 99%